Antimicrobial Activities of Some Marine Macroalgae Species from Iskenderun Bay - Selin Sayın (Turkish Journal of Agriculture: Food Science and Technology)
In the present study, the seaweeds belong to Phaeophyaceae (Halopteris scoparia (Linnaeus) Sauvageau 1904, Cystoseria mediterranea Sauvageau 1912), Rhodophaceae (Liagora viscida (Forsskål) C.Agardh 1822, Laurencia nidifica J.Agardh 1852) and Chlorophyceae (Enteromorpha multiramosa Bliding, nom. inval. 1960) collected from nearby Iskenderun-Turkey of Mediterranean Sea were detected for their antimicrobial activities against seven bacterial (Escherichia coli ATCC 35218, Bacillus cereus NRRL B-371, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Klebsiella pneumoniae ATCC 13883, Salmonella typhimurium ATCC 14028, Proteus vulgaris RSKK 96029) and three fungal strains (Candida albicans ATCC 10231, C. krusei ATCC 6258, C. tropicalis Y-12968). The antimicrobial activities were expressed as minimum inhibitory concentrations (MICs), minimum bacterial concentrations (MBCs) and minimum fungicidal concentrations (MFCs) were determined. According to the results obtained from MIC values of the extracts on pathogenic microorganisms were between 50 and 50 and